2017
DOI: 10.1021/acs.analchem.6b04852
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of an HPV Type-16 Specific Modified DNA Aptamer for the Improvement of Potency Assays

Abstract: Measuring vaccine potency is critical for vaccine release and is often accomplished using antibody-based ELISAs. Antibodies can be associated with significant drawbacks that are often overlooked including lot-to-lot variability, problems with cell-line maintenance, limited stability, high cost, and long discovery lead times. Here, we address many of these issues through the development of an aptamer, known as a slow off-rate modified DNA aptamer (SOMAmer), which targets a vaccine antigen in the human papilloma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Tuberculosis [9] H63SL2-M6 HspX Aptamer linked immobilized sorbent assay and electrochemical sensor Tuberculosis [18] Thiolated MPT64 aptamer MPT64 Combination of aptamers and electrochemical impedance spectroscopy Tuberculosis [19] MAA I and MAA II MPT64 A sandwich-type electrochemical aptasensor Salmonella [10] LA27 LPS Truncated aptamer LA27 combined with GO-based FP assays Salmonella [20] Apt-E. coli Apt-S. typ E. coli S. typ Aptamer modified by fluorescent magnetic multifunctional nanoprobe (APT-FMNPs) S. aureus [21] Chimeric [33] HCVcp ssDNA aptamer HCVcp A plasmonic nanoplatform Human papillomavirus [34] HPV16 L1 ssRNA aptamer HPV16 L1 protein The laser desorption/ionization mass spectrometry method Human papillomavirus [35] HPV-07 HPV16 virus-like particle (VLP) Slow abscission rate-modified DNA aptamer Influenza [37] NP-specific aptamer, CTnI-specific aptamer Influenza nucleoprotein (NP) and cardiac troponin I (cTnI).…”
Section: Bacterial Types Aptamer Target Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuberculosis [9] H63SL2-M6 HspX Aptamer linked immobilized sorbent assay and electrochemical sensor Tuberculosis [18] Thiolated MPT64 aptamer MPT64 Combination of aptamers and electrochemical impedance spectroscopy Tuberculosis [19] MAA I and MAA II MPT64 A sandwich-type electrochemical aptasensor Salmonella [10] LA27 LPS Truncated aptamer LA27 combined with GO-based FP assays Salmonella [20] Apt-E. coli Apt-S. typ E. coli S. typ Aptamer modified by fluorescent magnetic multifunctional nanoprobe (APT-FMNPs) S. aureus [21] Chimeric [33] HCVcp ssDNA aptamer HCVcp A plasmonic nanoplatform Human papillomavirus [34] HPV16 L1 ssRNA aptamer HPV16 L1 protein The laser desorption/ionization mass spectrometry method Human papillomavirus [35] HPV-07 HPV16 virus-like particle (VLP) Slow abscission rate-modified DNA aptamer Influenza [37] NP-specific aptamer, CTnI-specific aptamer Influenza nucleoprotein (NP) and cardiac troponin I (cTnI).…”
Section: Bacterial Types Aptamer Target Methodsmentioning
confidence: 99%
“…Several problems of antibodies like batch variability, limited stability, and long discovery lead time were overcome by developing slow abscission rate-modified DNA aptamer (SOMAmer), which targets antigens in the HPV vaccine [35]. An HPV-07 aptamer was selected to bind to the type 16 virus-like particle (VLP) formed by the self-assembled capsid protein L1.…”
Section: Human Papillomavirusmentioning
confidence: 99%
“…In a similar approach, a SOMAmer named HVP-07 was selected against the Type 16 virus-like particle (VLP) and used in a sandwich-like mix and read assay. The use of SOMAmers in this assay greatly improved the simplicity of the system (no wash steps required) and allowed for a fast read-out [ 124 ].…”
Section: Strategies For Improving Binding Affinity Through Chemicamentioning
confidence: 99%
“…When this aptamer was used in ELISA, the aptamer showed very high specificity. They demonstrated that this assay format offered more time and required fewer resources than traditional ELISA [10]. Aspermair et al developed a reduced graphene oxide-based field-effect transistor (rGO-FET) for detecting the HPV E7 protein in saliva using RNA aptamers.…”
Section: Aptamers For Hpv Diagnosticsmentioning
confidence: 99%